2021
DOI: 10.3389/fsurg.2021.663128
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction of NPVR ≥ 80% of Ultrasound-Guided High-Intensity Focused Ultrasound Ablation for Uterine Fibroids

Abstract: Objective: To evaluate factors in predicting the treatment outcome of ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation for uterine fibroids with a non-perfused volume ratio (NPVR) of at least 80%.Methods: One thousand patients with uterine fibroids who received USgHIFU were enrolled. Thirty-two independent variables of four dimensions of data set, including general information of patients, clinical symptoms, laboratory tests, and fibroid imaging characteristics, were used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Park et al ( 31 ) reported that HIFU ablation of uterine fibroids achievement of an immediate NPVR of at least 80% was safe, with greater tumor volume shrinkage compared with cases with a lower NPVR. Recently, some scholars have set NPVR at least 80% as a measure of sufficient ablation indexes in HIFU treatment of uterine fibroids ( 32 ). In addition, some scholars investigated MRI screening parameters for predicting an NPV ratio of at least 90% ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al ( 31 ) reported that HIFU ablation of uterine fibroids achievement of an immediate NPVR of at least 80% was safe, with greater tumor volume shrinkage compared with cases with a lower NPVR. Recently, some scholars have set NPVR at least 80% as a measure of sufficient ablation indexes in HIFU treatment of uterine fibroids ( 32 ). In addition, some scholars investigated MRI screening parameters for predicting an NPV ratio of at least 90% ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, researchers have set the NPVR at a minimum of 80% as a measure of sufficient ablation in the HIFU ablation therapy of uterine fibroids. 25,26 Even some researchers have shown that an NPVR of 90% can be used as a standard for the HIFU ablation therapy of uterine fibroids. 15,16 Among the 20 centres included in this current study, the aim was to obtain a higher NPVR on the premise of safety, so as to improve the clinical effect of HIFU ablation of uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Recently, researchers have set the NPVR at a minimum of 80% as a measure of sufficient ablation in the HIFU ablation therapy of uterine fibroids. 25 , 26 Even some researchers have shown that an NPVR of 90% can be used as a standard for the HIFU ablation therapy of uterine fibroids. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies showed that hyperintense fibroids could also be ablated with more ultrasonic energy than other signal intensity fibroids ( 7 , 8 ). Recently, a study proposed that the signal intensity on T2WI was the most important factor affecting ablative efficiency ( 9 ). Therefore, whether HIFU ablation is suitable for hyperintense fibroids on T2WI and which treatment protocol should be adopted has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%